Economic crisis and support for progressive taxation in Europe. Issue 2 (15th March 2019) - Garcia-Muniesa, Jordi
ABSTRACT: In this article, I discuss whether changes in European citizens' financial circumstances during the Great Recession have affected their attitudes towards tax progressivity. I analysed data from a 2015 survey of citizens in 9 European countries that gathered information about the economic crisis at the household level and citizens' preferences for tax progressivity. Results revealed that although citizens affected by the crisis were generally more likely to support progressive taxation, the impact of worsening economic circumstances was limited and not homogeneous across the sampled population. Citizens on the left of the ideological spectrum who suffered the economic setback did not show higher support for progressive taxation, while those in the centre and on the right did. Similarly, citizens who perceived their financial setbacks to be temporary and were optimistic about their economic prospects did not indicate increased support for tax progressivity, as opposed to those less optimistic about their future economic situation.